Identification of clinker formation in power station boilers – CFD based approach - Kotadiya, Nilesh Chandulal (Curtin University, 2010)
Pulverised coal combustion continues to be one of the main conventional methods of producing electricity over the last several decades. Mineral matter present in coal is usually present as free ions, salts, organically bound inorganic and hard minerals. During coal combustion these minerals partly vaporized, coalesce or fragment. The mineral matter in coal transforms into ash during combustion and deposition on wall surfaces causing problems such as fouling and slagging. The deposited lumps called clinkers, mainly in radiation zone directly exposed to flame radiation resulting to slagging, while sintered deposit in convection zone not directly exposed by flame radiation called fouling. The scope of this work encompasses identification of slagging and clinker formation areas in a typical 330 MW boiler using commercial code FLUENT and several available empirical indices. The propensity of the slagging with the used coal is calculated by several thermal indices. Temperature distributions, velocity profiles and particle trajectories were analysed and utilised to predict the most probable zones likely to experience clinker formation. Most probable spots for slagging were found in the radiation zone near to the nose of furnace and left-top side of superheater tube sections which agrees closely with the plant observations. However, the propensity of deposited ash obtained from the plant is seemed low to medium using several indices.Results from the current investigation demonstrate the usefulness of modelling approach in identifying the probable zones of clinker formation which can prove to be valuable for power utilities to adopt corrective measures for soot blowing to clean the ash deposits before it grows bigger in size.